Kinsenoside Ameliorates Oxidative Stress-Induced RPE Cell Apoptosis and Inhibits Angiogenesis via Erk/p38/NF-κB/VEGF Signaling - Luo, Xu; Gu, Shengjie; Zhang, Yujiao; Zhang, Jianhong (Frontiers in Pharmacology, 2018)
The pathological superoxidative condition that retinal pigment epithelium (RPE) cells experience contributed to the advancement of age-related macular degeneration (AMD), which was accompanied by significant neovascularization. Therefore, the discovery of novel pharmacological candidates to ameliorate oxidative damage (H2O2) against RPE cells and inhibit the following angiogenesis simultaneously is urgently needed. Herein, we found that kinsenoside (Kin), an active component derived from Anoectochilus roxburghii, was able to protect RPE cells effectively and attenuate subsequent angiogenesis. In this study, H2O2-induced oxidative injury reduced RPE cell viability and increased cell apoptosis, which was significantly rescued by the treatment with Kin. Compared with H2O2 alone, Kin decreased the levels of Bax and increased the production of Bcl-2 in RPE cells. H2O2-stimulated VEGF up-regulation was inhibited by Kin treatment. HUVEC neovascularization induced by conditioned medium (CM) from H2O2-stimulated RPE cells was attenuated by treatment with Kin, VEGF antagonist, NF-κB, Erk-MAPK and p38-MAPK inhibitors. Additionally, H2O2-activated phosphorylated expression of IκBα, p65, Erk and p38 in RPE cells was inhibited by treatment with Kin. Taken together, Kin protected RPE from apoptosis against oxidative stress while simultaneously decreasing apoptosis-related neovascularization. This could be ascribed to the inhibition of Erk/p38/NF-κB signaling by Kin that contributed to the resulting decreased VEGF expression in H2O2-treated RPE cells.